Виявлення і реалізація потенціалу студента при вивченні вищої математики - Олексенко, Вячеслав Михайлович (НТУ "ХПІ", 2012)
The results of a pedagogical experiment concerning revealing and realizing tudents'potential are listed. 328 students of a control and experimental groups took part in the experiment. It is determined that studying which is oriented at aim-directed systematic selfrealization is provided in unity of intellectual, physical and humane development at studactive lessons. The components of this process and basic skills of students are revealed. According to McNamara criterion it is proved that using studactive lessons by studying higher mathematics favors self-realization of students.
Keywords: вища математика; навчання; самореалізація; студенти